Regorafenib Versus Nivolumab After Sorafenib Failure: Real‐World Data in Patients With Hepatocellular Carcinoma. Issue 7 (16th June 2020) - Choi, Won‐Mook; Choi, Jonggi; Lee, Danbi; Shim, Ju Hyun; Lim, Young‐Suk; Lee, Han Chu; Chung, Young‐Hwa; Lee, Young‐Sang; Park, Sook Ryun; Ryu, Min‐Hee; Ryoo, Baek‐Yeol; Lee, So Jung; et al.
Abstract : Regorafenib and nivolumab are drugs approved for second‐line treatment of patients with hepatocellular carcinoma (HCC) after sorafenib failure. However, the effectiveness of regorafenib and nivolumab following sorafenib has not been directly compared. This study retrospectively evaluated 373 patients with HCC who were treated with regorafenib (n = 223) or nivolumab (n = 150) after sorafenib failure between July 2017 and February 2019. Progression‐free survival (PFS; hazard ratio [HR], 0.85; 95% confidence interval [CI], 0.69‐1.06; P = 0.150), time to progression (TTP; HR, 0.95; 95% CI, 0.77‐1.19; P = 0.680), and overall survival (OS; HR, 0.83; 95% CI, 0.64‐1.07; P = 0.154) did not differ significantly between groups of patients treated with regorafenib and nivolumab, findings consistently observed by multivariable‐adjusted, propensity score‐matched, and inverse probability treatment weighting (IPTW) analyses. However, the objective response rate was significantly higher in the nivolumab than in the regorafenib group (13.3% vs. 4.0%; P = 0.002). When the effectiveness of regorafenib and nivolumab was compared in nonprogressors to treatment, defined as patients who achieved complete response, partial response, or stable disease after first response evaluation, PFS (HR, 0.50; 95% CI, 0.33‐0.75; P = 0.001), TTP (HR, 0.48; 95% CI, 0.31‐0.73; P < 0.001), and OS (HR, 0.51; 95% CI, 0.31‐0.87; P = 0.013) were significantly longer in the 59 nonprogressors to nivolumab than in the 104 nonprogressors to regorafenib, findings also observed by multivariable‐adjusted and IPTW analyses. Conclusion: Survival outcomes in patients treated with regorafenib and nivolumab after sorafenib failure did not differ significantly. However, nivolumab may be more effective than regorafenib in nonprogressors. Abstract : In this retrospective comparative study, the effectiveness of regorafenib and nivolumab following sorafenib in HCC was investigated. The oncological outcomes were not different between the regorafenib and nivolumab groups. However, nivolumab showed better outcomes than regorafenib when progressors to each were excluded.